Knee synovitis, their treatment in the therapeutic room at the Faculty of Physical Culture «Nancy Uranga Romagoza» - Annia Gómez Valdés; Yakelin Mendoza Cabrera; Leidys Escalante Cambeaux (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2018)
This work is aimed at proposing therapeutic exercises and massages to contribute to the treatment of the knee synovitis in patients who  assisted tothe therapeutic area of the Physical Culture Faculty «Nancy UrangaRomagoza», Pinar del Río; Taking into account that in spite of a month of treatment the patients presented limitation to articulate, reduction of the walk motion and decrease of the muscular tone of the muscles that participate in the movements of that articulation, influencing negatively in the rehabilitation of their injury. The usage of theoretical methods as historical-logical, analysis-synthesis and inductive-deductive; of empiric methods as the analysis with documents and the measuring experiment, as well as the statistical methods, facilitated to verify the limitations in the joint width around the injured knee, also to structure the proposal whose therapeutic exercises having as a principle, the regulation of the loads increasing gradually the complexity levels, structured in two stages, initial and advanced, as well as the linking to the massage, in such way that impacts positively in the patient's recovery. In the conclusions there is a reference to the importance of the patient´s active participation on behalf of the effectiveness of the therapy and it is recommended to continue the study of the factors that determine a better rehabilitation treatment for patients suffering knee synovitis.